Optimal control and the Fibonacci sequence - Thomas von Brasch; Johan Byström; Lars Petter Lystad (Statistics Norway, Research Department, 2012)
We bridge mathematical number theory with that of optimal control and show that a generalised Fibonacci sequence enters the control function of finite horizon dynamic optimisation problems with one state and one control variable. In particular, we show that the recursive expression describing the first-order approximation of the control function can be written in terms of a generalised Fibonacci sequence when restricting the final state to equal the steady state of the system. Further, by deriving the solution to this sequence, we are able to write the first-order approximation of optimal control explicitly. Our procedure is illustrated in an example often referred to as the Brock-Mirman economic growth model.
Keywords: C6; 330; Fibonacci sequence; Golden ratio; Mathematical number theory; Optimal control.